11b-2(b-9)=36

Simple and best practice solution for 11b-2(b-9)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11b-2(b-9)=36 equation:


Simplifying
11b + -2(b + -9) = 36

Reorder the terms:
11b + -2(-9 + b) = 36
11b + (-9 * -2 + b * -2) = 36
11b + (18 + -2b) = 36

Reorder the terms:
18 + 11b + -2b = 36

Combine like terms: 11b + -2b = 9b
18 + 9b = 36

Solving
18 + 9b = 36

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 9b = 36 + -18

Combine like terms: 18 + -18 = 0
0 + 9b = 36 + -18
9b = 36 + -18

Combine like terms: 36 + -18 = 18
9b = 18

Divide each side by '9'.
b = 2

Simplifying
b = 2

See similar equations:

| 7x-3+7x=-151 | | 7c-3+7x=-151 | | -0.25x^2+223x-45760=0 | | 223x-0.25x^2-180=0 | | 5x+5+5x=-55 | | -6+4x-5x=-10 | | 2085000000.00+5550000.00=2500000000 | | 2.3x+5=-5.4 | | 11x-x^2-18=0 | | 5-2x=4x-9 | | -4-7x+3x=-24 | | -0.25x^2+223x-180=0 | | 7-4x+x=28 | | 4q^2-4mq= | | -8x^2+176x-320=0 | | 5x+2+5x=-8 | | 9=4x+3x-5 | | 2x^2-36x+4=0 | | 24x-21=33 | | -10-3x-3x=-70 | | -110+6x=-110+6x | | x+10+7x=34 | | 3x(4+7)-9y= | | findg(x)=6x^3-43x^2+6x+7for | | -7x-3+6x=3 | | f=5g | | b=12-a | | 2x+2+5x=-75 | | 25n+15n^2= | | 50=4x+3x+8 | | (15x+2)(15x-2)=225x-4 | | 5x=x+12 |

Equations solver categories